2020
DOI: 10.3390/v12070720
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus in Slovenia

Abstract: West Nile virus (WNV) is a flavivirus transmitted by mosquitoes. Birds are the reservoir for the virus; humans, horses and other mammals are dead-end hosts. Infections caused by WNV in humans can vary from asymptomatic infections to West Nile fever (WNF) or West Nile neuroinvasive disease (WNND). In 1995, a serosurvey was performed in Slovenia on forest workers, and WNV specific IgG antibodies were confirmed in 6.8% of the screened samples, indicating that WNV is circulating in Slovenia. No human disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The first case was confirmed in 2013 in a patient with meningitis. Thereafter, in 2018, three cases of WNND were confirmed by detection of IgM antibodies in the CSF samples (99). In 2009, 481/1912 (25.2%) clinically healthy horses were positive for WNV IgG antibodies (100).…”
Section: Sloveniamentioning
confidence: 99%
“…The first case was confirmed in 2013 in a patient with meningitis. Thereafter, in 2018, three cases of WNND were confirmed by detection of IgM antibodies in the CSF samples (99). In 2009, 481/1912 (25.2%) clinically healthy horses were positive for WNV IgG antibodies (100).…”
Section: Sloveniamentioning
confidence: 99%
“…mosquitos was found to be positive by RT-PCR in 2018, but negative in 2017 and 2019. A sentinel study on dog sera samples confirmed WNV antibodies by an indirect immunofluorescence study in 1.8 and 4.3% of samples collected in 2017 and 2018, respectively ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, birds that become infected may develop symptoms arising from the infection. The first positive active cases of WNV in people in Slovenia were detected in 2018 in three patients with IgM antibodies in the cerebrospinal fluid of the patients [ 2 ]. In animals, the first active cases of WNV in Slovenia were detected in a hooded crow ( Corvus cornix ) and a horse in the Ljubljana region in 2018 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, the first cases of USUV in Slovenia were detected in a common blackbird ( Turdus merula ) and a song thrush ( Turdus philomelos ) [ 4 ]. Based on the successful virus isolation and complete genome sequencing, connection between positive human cases and WNV found in mosquitos has been made [ 2 ]. Additionally, the whole genome sequence indicates that virus most likely spread from the north because of the geographic proximity as well as the sequence cluster with the Austrian and Hungarian sequences [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation